Creation of a systematic interdental brush set based on the passage hole diameter (PHD): an in-vitro study - Sekundo, Caroline; Ottensmeier, Friederike; Rues, Stefan; Staehle, Hans Jörg; Pujades, Manuel; Frese, Cornelia (Oral health & preventive dentistry, 2024)
Purpose: This study aimed to develop a systematic interdental brush set with size distribution based on the passage hole diameter (PHD), addressing existing gaps in size selection criteria for effective interdental cleaning. Materials and Methods: In the first step, an interdental brush set that ascends stepwise according to the PHD value was envisioned. The study was divided into three phases: (i) in-vitro determination of PHD values of a currently existing assort-ment on the market by 13 calibrated dental professionals, (ii) in-vitro assessment of forces during insertion, and (iii) cre-ation and evaluation of new prototypes for missing or non-matching PHD sizes. Intra- and inter-rater reliability, assessed with the intraclass correlation coefficient (ICC), as well as insertion forces and PHD sizes at all stages were reported. Results: In the existing range, three interdental brushes fitting the desired PHD sizes were initially identified. Mean insertion forces between 0.3 and 1.7 N were documented based on raters' PHD choices. Two additional rounds of measurements with prototypes adapted in diameter and shape were necessary, particularly for PHD values of 1.4, 2.3 and 2.6. High intra- and in-ter-rater reliability was observed throughout the study (ICC > 0.95), ensuring consistent evaluations. After three rounds of as-sessments, a prototype was successfully identified for each targeted PHD value in the systematised set, showcasing reliable sizing and insertion forces. Conclusion: Using a structured approach, a comprehensive interdental brush set was developed with reliable PHD sizing and moderate insertion forces. The verification of size reliability through measurements by dentists represents a novelty in development and underlines the importance of accurate brush size selection for optimal biofilm control. Whether a systematic set based on the PHD value offers added value for clinical practice, and at what intervals, must be demon-strated in further studies.